Pengembangan Aplikasi Veggieku Sebagai Solusi Digitalisasi Transaksi UMKM Sayuran: Studi Kasus Pada UD Dunia Dagang - Putra Pangestu, Dhamar; Adji, Sanuri; Juniansyah, Zaki (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy, yet many still have not fully utilized digital technology in their business processes. UD Dunia Dagang, as one of the MSMEs engaged in vegetable sales, still conducts transactions conventionally, resulting in inefficiencies and limitations in sales data recording. This internship project aims to develop an application called VeggieKu as a digital solution for transactions at UD Dunia Dagang.